Feasibility Study of Waste Rock Wool Fiber as Asphalt Mixture Additive: Performance Test and Environmental Effect Analysis - Bingjian Zeng; Ni Wan; Sipeng Zhang; Xiaohua Yu; Zhen Zhang; Jiawu Chen; Bin Lei (Buildings)
To investigate the feasibility of utilizing waste rock wool fiber as an additive in asphalt mixtures for resource recycling, this study evaluates and analyzes the performance of asphalt and asphalt mixtures, as well as their environmental benefits. Initially, the properties and mechanisms of modified asphalt mortar are examined under different shapes (powdery rock wool fiber (RWP) and fibrous rock wool fiber (RWF)) and varying rock wool fiber contents (0%, 1%, 2%, 3%, and 4% of matrix asphalt mass). Subsequently, the pavement performances of asphalt mixtures with different RWF contents (0%, 0.1%, 0.2%, 0.3%, and 0.4% of asphalt mixture mass) are compared. The environmental and economic impacts of RWF-modified asphalt mixtures are assessed using the life cycle assessment (LCA) method and the benefit cost analysis (BCA) method. Finally, the carbon property ratio (CPR), an innovative index, is proposed. It comprehensively evaluates the pavement performances and economic benefits of RWF modified asphalt mixtures in relation to carbon emissions (CEs). The results indicate that compared to RWP, RWF primarily functions as an inert fiber stabilizer. It provides a physical reinforcing effect through its three-dimensional network skeleton structure. Both RWP and RWF-modified asphalts exhibit improved performance compared to matrix asphalt. RWF demonstrates superior temperature susceptibility and high temperature performance. The optimal contents for achieving the best high temperature, water stability, and low-temperature crack resistance performances of RWF-modified asphalt mixtures are 0.3%, 0.2%, and 0.2%, respectively. As the RWF content increases, the energy consumption (EC) and CEs during the pavement construction stage slightly rise within an acceptable range, while positive economic benefits also increase. Additionally, the CPR index can comprehensively assess the favorable effects of pavement performances or economic benefits against the adverse effects of CEs. It offers theoretical guidance for the design of optimal rock wool fiber content.